The Effect of Rope Skipping Training On Shooting Ability To The Goal of Futsal Game Students UPT SPF SMPN 46 Makassar - Muh. Nuryadin; Herman Herman; Muhammadong Muhammadong; M. Adam Mappaompo; Muh. Adnan Hudain (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research is experimental research with a quantitative approach. This study aims to determine whether there is a difference between rope skipping using one foot and rope skipping using two feet using two feet on the shooting ability of UPT SPF SMPN 46 Makassar students. The sample in this study amounted to 28 athletes which were divided into 14 athletes with one-foot rope skipping treatment and 14 athletes with two feet rope skipping treatment. with two-legged rope skipping treatment foot with shooting test instruments using 9 times shot into the goal. The research method is used to looking for the effect of certain treatments on others under controlled conditions or experimental methods. controlled conditions or experimental methods. The results of this study are. With the results of the study, the effect of of 2-leg rope skipping training amounted to 53.9% on shooting ability, and the effect of 1-foot rope skipping training to 52.7% on shooting ability Conclusion. Increase in rope training skipping with 6,550 for rope skipping 2 feet and 2,900 for rope skipping 1 foot. The study concludes that the 2-foot rope skipping exercise has a higher increase than the 1-foot rope skipping.